On Self-Scaling Variable-Metric Algorithms - Abbas Al-Bayati; Mardin Taher (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we have developed a new self-scaling VM-method for solving unconstrained nonlinear optimization problems. The numerical and theoretical results demonstrate the general effectiveness of the new self-scaling VM-method when compared with  PHUA  &  ZENG  algorithm ; we have tested these algorithms on several high-dimension test functions with promising numerical results.